Augmented Reality in Breaststroke Swimming: Improving Techniques and Skills - Rahayu, Tri Winarti; Rozi, Fatkhur; Nasir, Muhammad Zulqarnain Mohd; Priyono, Bambang; Difa, Khalil Junan (Faculty of Sport and Health Sciences, 2024)
This study aims to assess the impact of Augment Reality (AR) media on breaststroke swimming skills in students of the Faculty of Sports, Sebelas Maret University Surakarta. The research method used in this study is a pseudo-experimental method. The research design implemented was a nonequivalent control group design. The study involved 30 students as subjects. Data collection in this study using breaststroke swimming skills test. The data analysis used was an intergroup t-test (independent t-test), which distinguishes breaststroke swimming skills between the experimental group and the control group. The experimental group received breaststroke swimming lessons using AR media, while the control group was taught breaststroke swimming with conventional methods. The results of this study indicated a significant difference in breaststroke swimming skills between the experimental group and the control group. Data were analysed using paired sample t-test and N-Gain Score. The results of this research showed the average results of the N-Gain Score calculation in the experimental group (60.6%) and the control group (30.6%). This shows that breaststroke swimming learning media using AR media is more effective than learning media with conventional media. The conclusion in this study is that learning breaststroke swimming using AR media has a significant effect on improving breaststroke swimming skills in students of the Faculty of Sports, Sebelas Maret University, Surakarta.